Passive sampling methods for contaminated sediments: State of the science for organic contaminants. (18th February 2014) - Lydy, Michael J; Landrum, Peter F; Oen, Amy MP; Allinson, Mayumi; Smedes, Foppe; Harwood, Amanda D; Li, Huizhen; Maruya, Keith A; Liu, Jingfu; Parkerton, Thomas F; Maruya, Keith A
ABSTRACT This manuscript surveys the literature on passive sampler methods (PSMs) used in contaminated sediments to assess the chemical activity of organic contaminants. The chemical activity in turn dictates the reactivity and bioavailability of contaminants in sediment. Approaches to measure specific binding of compounds to sediment components, for example, amorphous carbon or specific types of reduced carbon, and the associated partition coefficients are difficult to determine, particularly for native sediment. Thus, the development of PSMs that represent the chemical activity of complex compound–sediment interactions, expressed as the freely dissolved contaminant concentration in porewater (Cfree), offer a better proxy for endpoints of concern, such as reactivity, bioaccumulation, and toxicity. Passive sampling methods have estimated Cfree using both kinetic and equilibrium operating modes and used various polymers as the sorbing phase, for example, polydimethylsiloxane, polyethylene, and polyoxymethylene in various configurations, such as sheets, coated fibers, or vials containing thin films. These PSMs have been applied in laboratory exposures and field deployments covering a variety of spatial and temporal scales. A wide range of calibration conditions exist in the literature to estimate Cfree, but consensus values have not been established. The most critical criteria are the partition coefficient between water and the polymer phase and the equilibrium status of the sampler. In addition, the PSM must not appreciably deplete Cfree in the porewater. Some of the future challenges include establishing a standard approach for PSM measurements, correcting for nonequilibrium conditions, establishing guidance for selection and implementation of PSMs, and translating and applying data collected by PSMs. Integr Environ Assess Manag 2014;10:167–178. © 2014 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of SETAC.